Land Ownership Rights for Indonesian Citizens of Chinese Descent in the Province of the Special Region of Yogyakarta - Syailendra Putra, Moody Rizqy; Joeliant, Hanz Bryan; Raditya, Anthonio Bimo (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
All Indonesian citizens have the right to own land in Indonesia according to the BAL and the 1945 Constitution. However, in the DIY Province, Indonesian citizens of Chinese descent are prohibited from owning land rights as regulated in the Instruction of the Head of the Special Region of Yogyakarta Number K.898/I/A/1975. This research discusses the legal provisions governing land ownership rights for Indonesian citizens of Chinese descent in the Province of DIY. The research method is normative with secondary data through primary and secondary legal materials. The approach used is statutory and historical with a prescriptive analysis using deductive logic. Based on the 1945 Constitution of the Republic of Indonesia which is discussed further in the UUPA, all Indonesian citizens can obtain property rights. There are historical factors contained so that the privilege law is enacted. This regulation was made to prevent exploitation of land in DIY and for the welfare of the people at that time.